Making the world over : confronting racism, misogyny, and xenophobia in U.S. history - Griffith, R. Marie (Ruth Marie), 1967- (University of Virginia Press, 2021)
"Making the World Over examines the histories behind the issues at the root of our nation's conflicts both past and present, from race and immigration to misogyny and reproductive rights, in an attempt to encourage constructive dialogue"-- Provided by publisher.
Keywords: Xenophobia -- United States -- Historiography.; Racism -- United States -- Historiography.; Misogyny -- United States -- Historiography.; Minorities -- United States -- Social conditions.; National characteristics, American.; United States -- Race relations -- Historiography.; United States -- Ethnic relations -- Historiography.; Xénophobie -- États-Unis -- Historiographie.; Racisme -- États-Unis -- Historiographie.; Misogynie -- États-Unis -- Historiographie.; États-Unis -- Relations raciales -- Historiographie.; États-Unis -- Relations interethniques -- Historiographie.; HISTORY / United States / 21st Century; Ethnic relations -- Historiography; Minorities -- Social conditions; National characteristics, American; Race relations -- Historiography; Racism -- Historiography; United States; Electronic books.